AGE-RELATED CHANGES IN HEART RATE VARIABILITY AND THEIR RELATION WITH LEUCOCYTE TELOMERE LENGTH - L. I. Streltsova; О. N. Tkacheva; E. V. Plokhova; D. U. Akasheva; I. D. Strajesko; E. N. Dudinskaya; S. А. Boytsov (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To assess the  relation of age-depended changes  in heart  rate variability (HRV) with telomere  length.  With the  age,  even  with no cardiovascular  diseases (CVD), there  is a decline of HRV which is an indicator of vegetative system condition. The probable  mechanism  for age-related decrease  in HRV might be  cellular ageing.  One  of the markers of cellular ageing is telomere length regarded  as a marker of biological age.Material and methods. Totally, 229 persons of age 23-91 y.o. included, with no clinical signs of cardiovascular diseases. All participants underwent the HRV analysis by the data of Holter ECG monitoring and of short ECG recordings supine and upright position by 5 minutes. Telomere length was assessed in leucocytes on genomic desoxyribonucleic acid (DNA) with plymeraze chain reaction  real time. The participants  were selected  to two groups: <60 y.o. and ≥60 y.o. Comparative analysis was done,  of the  parameters  studied,  in two age  groups,  correlational analysis  of telomere  length  with HRV, linear regression  analysis  and multiple regression.Results. In the group of the older, telomere length was higher than in the  younger  — 9,90±0,47  units vs 9,65±0,43  units (p<0,001)  with close correlation of telomere length with the age (r=-0,32, p<0,05). By the data  of linear regression,  telomere  length is closely related with the mean value of standard deviations of all selected  RR intervals for every 5 minutes of 24-hour recording (SDANN), with the power of high-frequency spectrum  (HF), relation of lowerand high-frequency waves (L/H) (β=0,36,  p=0,006; β=0,39,  p=0,004; β=-0,32,  р=0,02, resp.). In older persons, in the group of shorter telomeres there were significantly lower values of mean standard  deviations for all selected R-R-intervals (SDNN) (111  (94;  126)  ms  vs 122  (112;  122)  ms), mean-square differences  between  the  duratons  of the  next  sinus intervals RR (RMSSD) R-R (RMSSD) — 16 (11; 22) ms vs 22 (17; 25) ms), power of the very low frequency spectrum  components  (VLF) — 1176 (718; 1453) ms2   vs 1476 (850; 1763) ms2)  by the  data  from Holter ECG, than in the group of longer telomeres (p<0,05). Differences by the shorter  recordings  supine  and  upright were not significant. Conclusion. Telomere length is related to the age-relevant HRV changes. Telomere  length  might  be  an  early  predictor  of the  ageassociated weakening of autonomous  regulation of heart  functioning and reflect real biological age of vegetative nervous system irrelevant to other cardiovascular risk factors.